Proceedings of the fifth international RASopathies symposium: When development and cancer intersect. Issue 12 (10th October 2018) - Rauen, Katherine A.; Schoyer, Lisa; Schill, Lisa; Stronach, Beth; Albeck, John; Andresen, Brage S.; Cavé, Hélène; Ellis, Michelle; Fruchtman, Steven M.; Gelb, Bruce D.; Gibson, Christopher C.; Gripp, Karen; et al.
Abstract : This report summarizes and highlights the fifth International RASopathies Symposium: When Development and Cancer Intersect, held in Orlando, Florida in July 2017. The RASopathies comprise a recognizable pattern of malformation syndromes that are caused by germ line mutations in genes that encode components of the RAS/mitogen‐activated protein kinase (MAPK) pathway. Because of their common underlying pathogenetic etiology, there is significant overlap in their phenotypic features, which includes craniofacial dysmorphology, cardiac, cutaneous, musculoskeletal, gastrointestinal and ocular abnormalities, neurological and neurocognitive issues, and a predisposition to cancer. The RAS pathway is a well‐known oncogenic pathway that is commonly found to be activated in somatic malignancies. As in somatic cancers, the RASopathies can be caused by various pathogenetic mechanisms that ultimately impact or alter the normal function and regulation of the MAPK pathway. As such, the RASopathies represent an excellent model of study to explore the intersection of the effects of dysregulation and its consequence in both development and oncogenesis.